Traditional Medicinal Plants as a Source of Antituberculosis Drugs: A System Review. (10th September 2021) - Xu, Yuhui; Liang, Bowen; Kong, Chengcheng; Sun, Zhaogang
Abstract : Medicinal plants are the chief components in the different oriental formulations in different traditional medical systems worldwide. As a thriving source of medicine, the medicinal plants with antituberculosis (TB) properties inspire the pharmacists to develop new drugs based on their active components or semimetabolites. In the present review, the anti-TB medicinal plants were screened from the scientific literatures, based on the botanical classification and the anti-TB activity. The obtained anti-TB medicinal plants were categorized into three different categories, viz., 159 plants critically examined with a total 335 isolated compounds, 131 plants with their crude extracts showing anti-TB activity, and 27 plants in literature with the prescribed formula by the traditional healers. Our systemic analysis on the medicinal plants can assist the discovery of novel and more efficacious anti-TB drugs.